The Case for NIT+FT in Europe: An Empirical Optimal Taxation Exercise - Nizamul Islam; Ugo Colombino (Institute of Labor Economics (IZA), 2017)
We present an exercise in empirical optimal taxation for European countries from three areas: Southern, Central and Northern Europe. For each country, we estimate a microeconometric model of labour supply for both couples and singles. A procedure that simulates the households' choices under given tax-transfer rules is then embedded in a constrained optimization program in order to identify optimal rules under the public budget constraint. The optimality criterion is the class of Kolm's social welfare function. The tax-transfer rules considered as candidates are members of a class that includes as special cases various versions of the Negative Income Tax: Conditional Basis Income, Unconditional Basic Income, In-Work Benefits and General Negative Income Tax, combined with a Flat Tax above the ex-emption level. The analysis show that the General Negative Income Tax strictly dominates the other rules, including the current ones. In most cases the Unconditional Basic Income policy is better than the Conditional Basic Income policy. Conditional Basic Income policy may lead to a significant reduction in labour supply and poverty-trap effects. In-Work-Benefit policy in most cases is strictly dominated by the General Negative Income Tax and Unconditional Basic Income.
Keywords: H21; C18; 330; optimal tax; negative income tax; basic income; micro-simulation; welfare